Modeling of PMSM with Multiple Saliencies Using a Stator-Oriented Magnetic Circuit Approach - Seilmeier, Markus; Piepenbreier, Bernhard (International Electric Machines and Drives Conference 2011 (IEMDC 2011), 2011)
Precise modeling of PMSM needs considering the nonlinear characteristics of the hard and soft magnetic materials used in the machine. Therefore nonlinear machine models with time-variant parameters are used. Usually saturation is modeled in the field oriented coordinates assuming that the d-axis flux affects the q-axis flux and vice versa. If certain conditions are fulfilled cross saturation inductances can occur. This paper introduces a new modeling approach to consider multiple geometric and saturation induced saliencies based on a stator-oriented magnetic circuit approach. The advantage of this method is that all kind of saliencies that occur in the electrical machine can be considered simultaneously. Moreover modeling in the stator coordinates leads to a physically motivated explanation when the cross saturation effect can occur in a PMSM. The result of the new modeling approach are new insights for the interpretation of the resulting inductances in the field oriented model. © 2011 IEEE.
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.LEEAS.modeli